How modern monetary theory questions the anxieties around debt - Jahangir, Junaid (My University, 2025)
Recently, top economists and historians assembled by the Peter G. Peterson Foundation sounded the alarm on the $38 trillion national debt in the US. The debt amounts to 120% of the GDP. However, Modern Monetary Theory (MMT) would reject this framing.
Keywords: US national debt crisis; Modern Monetary Theory (MMT); Peter G Peterson Foundation critique; Stephanie Kelton economics; US dollar hegemony; debt to GDP ratio explanation; monetary sovereignty; Reinhart and Rogoff austerity; US China